2017
DOI: 10.1038/srep44848
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive silicon nitride: A new therapeutic material for osteoarthropathy

Abstract: While the reciprocity between bioceramics and living cells is complex, it is principally governed by the implant’s surface chemistry. Consequently, a deeper understanding of the chemical interactions of bioceramics with living tissue could ultimately lead to new therapeutic strategies. However, the physical and chemical principles that govern these interactions remain unclear. The intricacies of this biological synergy are explored within this paper by examining the peculiar surface chemistry of a relatively n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 51 publications
2
47
0
1
Order By: Relevance
“…Similarly, the interaction between PEEK/β‐Si 3 N 4 and SaOS‐2 cells, which includes the elution of orthosilicate molecules from the Si 3 N 4 ceramic particles, is provided in Figure c; while in Figure d is an enlarged view of the chemical interaction between the cell membrane and the biological environment in the vicinity of the Si 3 N 4 particles. This last figure also envisages the formation of endocytotic vesicles around orthosilicate clusters and silicon quantum dots (Si‐QDs) which were detected in SaOS‐2 cell grown bony tissue reported in a previous study …”
Section: Discussionsupporting
confidence: 71%
“…Similarly, the interaction between PEEK/β‐Si 3 N 4 and SaOS‐2 cells, which includes the elution of orthosilicate molecules from the Si 3 N 4 ceramic particles, is provided in Figure c; while in Figure d is an enlarged view of the chemical interaction between the cell membrane and the biological environment in the vicinity of the Si 3 N 4 particles. This last figure also envisages the formation of endocytotic vesicles around orthosilicate clusters and silicon quantum dots (Si‐QDs) which were detected in SaOS‐2 cell grown bony tissue reported in a previous study …”
Section: Discussionsupporting
confidence: 71%
“…Load-bearing Si3N4 prosthetic hip bearings and spinal fusion implants were initially developed because of the superior strength and toughness of Si3N4 [50]. Later studies showed other properties of Si3N4 that are favored in designing orthopaedic implants, such as enhanced osteoconductivity [51][52][53][54] and bacteriostasis [14,[55][56][57][58][59][60]. Taken together, these data suggest that Si3N4's surface chemistry, previously known to contribute concurrent upregulation of osteogenic activity and prevention of bacterial adhesion and biofilm formation, is also quite effective against viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The PD output voltage was found to be stable throughout this period (not shown here). This work can be extended to perform biological assays as the nanophotonic sensors are made of silicon nitride which can be functionalized for a range of biosensing experiments [25], [26].…”
Section: Resultsmentioning
confidence: 99%